Six Exonic Variants in the SLC5A2 Gene Cause Exon Skipping in a Minigene Assay - Wang, Sai; Wang, Yixiu; Wang, Jinchao; Liu, Zhiying; Zhang, Ruixiao; Shi, Xiaomeng; Han, Yue; Guo, Wencong; Bottillo, Irene; Shao, Leping (Frontiers in Genetics, 2020)
Background: Familial renal glucosuria is a rare renal tubular disorder caused by SLC5A2 gene variants. Most of them are exonic variants and have been classified as missense variants. However, there is growing evidence that some of these variants can be detrimental by affecting the pre-mRNA splicing process. Therefore, we hypothesize that a certain proportion of SLC5A2 exonic variants can result in disease via interfering with the normal splicing process of the pre-mRNA. Methods: We used bioinformatics programs to analyze 77 previously described presumed SLC5A2 missense variants and identified candidate variants that may alter the splicing of pre-mRNA through minigene assays. Results: Our study indicated six of 7 candidate variants induced splicing alterations. Variants c.216C>A, c.294C>A, c.886G>C, c.932A>G and c.962A>G may disrupt splicing enhancer motifs and generate splicing silencer sequences resulting in the skipping of exon 3. Variants c.305C>T and c.1129G>A probably disturb splice sites leading to exon skipping. Conclusion: To our knowledge, we report, for the first time, SLC5A2 exonic variants that produce alterations in pre-mRNA. Our research reinforces the importance of assessing the consequences for putative point variants at the mRNA level. Additionally, we propose that minigenes function analysis may be valuable to evaluate the impact of SLC5A2 exonic variants on pre-mRNA splicing without patients’ RNA samples.